Konsep Dasar Zakat - Indah Fatmah Maulidiyah; Amalia Saharani; Savira Melia Putri; Nafisa Dhabita; Nur Wakhid (INDO PUBLISHING, 2026)
One of the cornerstones of Islam, zakat is significant not only in the spiritual realm but also in the social and economic spheres of society. Based on Islamic law and its application in Indonesia, this article addresses zakat's definition, legal foundation, categories, requirements, computation, and administration. As mentioned in QS. At-Taubah verse 60, it highlights the significance of comprehending the concepts of nisab and haul as well as the allocation of zakat to eight kinds of receivers. Zakat has a significant effect on lowering poverty and economic inequality in addition to its spiritual advantages. However, low public literacy, opaque zakat institutions, and legislative restrictions continue to be obstacles to zakat implementation in Indonesia. Therefore, for zakat to be a successful tool for creating a prosperous and just society, cooperation between education, policy reform, and institutional improvement is required.